108 Altered matrix adhesion, impaired function and mitochondrial hyperactivity in endothelial colony forming cells isolated from patients with diabetic foot ulcers. (June 2018) - Langford-Smith, AWW; Floren, M; Wei, T; Hasan, A; Weston, R; Edwards, N; Wilkinson, FL; Alexander, Yvonne; Rashid, ST; Bowling, F; Boulton, A
Abstract : Introduction: Patients with diabetes have impaired endothelial colony forming cell (ECFC or endothelial progenitor cell) function leading to poor vascular endothelial repair, potentially contributing to diabetic foot ulceration, a major health and economic burden. The objective was to characterise the functional deficit in these cells in order to understand the pathogenic mechanism and identify novel therapeutic targets. Methods: ECFCs were harvested from the peripheral blood of healthy controls and patients with diabetes and neuroischaemic foot ulcers using cell culture techniques. Functional and biochemical analyses of the migratory, angiogenic and metabolic activity were performed. In addition, a neotissue array was used to compare ECFC binding and growth to different matrix ligands (RGD, DGEA, IKVAV, YIGSR, VAPG) and combinations of ligands, including soft and fibrous matrices to represent distinct environments. Results: Neuroischaemic ECFCs take longer to form colonies on isolation, have impaired nitric oxide production (46% of control) and a reduced migratory response to SDF-1 (77% of control), decreased scratch closure (87% of control) and compromised tube formation (38% of control in the matrigel assay compared to healthy ECFCs). Seahorse extracellular flux analysis of metabolic function identified no change in glycolysis, but mitochondrial function and maximal oxygen consumption was increased two fold in the neuroischaemic ECFCs vs healthy ECFCs. The neotissue array revealed a decrease in binding of neuroischaemic and control ECFCs to stiff matrix compared to normal physiological stiffness by between a half and two thirds over 24 hours. The neuroischaemic ECFCs bound less, and to a reduced repertoire of matrix peptides compared to controls, suggesting a diminished binding capacity. Furthermore, in long-term culture the viability of neuroischaemic ECFCs was reduced compared to control cells. Discussion: This study is the first to describe the defect in matrix adhesion and metabolic changes in neuroischaemic diabetic ECFCs, which may contribute to impaired endothelial repair observed in vivo . Further work to characterise the mechanism of this binding deficiency will allow us to develop an improved model of disease in vitro, leading to identification of new therapeutic targets and stem cell therapies for wound healing.